Analysis of Mathematical Problem Solving Ability Viewed by Students Learning Motivation in PBL Learning Model Hijri Calendar Textbooks-Assisted - Rahmawati, Lusi; Munahefi, Detalia Noriza (Unnes Journal of Mathematics Education, 2023)
This study aims to examine classical mastery, average differences, and differences in proportions between PBL learning assisted by hijri calendar textbooks and PBL learning and describe mathematical problem-solving abilities in terms of students' learning motivation. This research is mixed method. The quantitative research samples were students of class X-8 (experimental group) and X-6 (control group) while in the qualitative research, the research subjects were taken from six students selected from the experimental group. Data collection was carried out by tests, questionnaires, interviews, and documentation. The results showed that (1) the ability to solve mathematical problems in the hijri calendar textbook-assisted PBL model achieved classical mastery, (2) the average mathematical problem-solving ability in the hijri calendar textbook-assisted PBL model was better than PBL learning, (3) the proportion of completeness of mathematical problem solving abilities in the PBL learning model assisted by hijri calendar textbooks is better than PBL learning, (4) a description of mathematical problem solving abilities in terms of students' learning motivation, namely: (a) students with high learning motivation have problem solving abilities very good, (b) students with medium learning motivation have fairly good problem-solving abilities, and (c) students with low learning motivation have poor problem-solving abilities.